Analysis Marital Quality and Parenting Style in Adolescence Marriage Family: Analysis Marital Quality and Parenting Style in Adolescence Marriage Family - Irmalia Noviani; Sri Ajrania; Fitri Ayu Wahyuni; Riany, Yulina Eva (Journal of Family Sciences, 2023)
Marriage during adolescence has an impact on the unpreparedness of families to carry out family duties and functions, including in building the quality of marriage and childcare. This study aims to analyze the quality of marriage and parenting styles in families who married in adolescence. This study used a phenomenological qualitative descriptive method using a purposive sampling technique. There were 3 participants in this study with criteria of mothers who married during adolescence and had children. This research was conducted in Purwakarta Regency in February-April 2022. Data collection techniques used observation, and semi-structured interviews with data analysis, reduction, and conclusion. The results showed that the quality of marriage in families who married in adolescence had low-quality marriages as indicated by poor communication between family members and low family economic conditions. In parenting styles, families generally adopt a permissive parenting style which is shown by giving warm affection to children but not accompanied by clear and consistent rules.